Experimental and numerical investigation on heat transfer enhancement of vertical triplex tube heat exchanger with fractal fins for latent thermal energy storage. (1st December 2022) - Shi, Shasha; Niu, Junyi; Wu, Ziheng; Luo, Shenghao; Gao, Xuenong; Fang, Yutang; Zhang, Zhengguo
Highlights: Experiment and numerical simulation were conducted for the vertical triplex tube heat exchanger with fractal fins. The heat transfer enhancement effect of latent thermal energy storage system using fractal fins is obviously better than that with rectangular fins. Compared with rectangular fins, optimized fractal fins increase the melting rate of phase change materials by 35.6%. The rational arrangement of charging and discharging process benefits from the dual-channel design, which makes the latent thermal energy storage system obtain better performance. Abstract: Latent thermal energy storage (LTES) technology applied in the recovery of industrial waste heat, solar thermal applications, and energy conversation of buildings, etc. can solve the mismatches of thermal energy in supply and demand, space and time, and thus increasing the efficiency of thermal energy utilization. However, the heat transfer process in a latent heat exchanger(LHE) is limited due to the poor thermal conductivity of phase change material (PCM). Therefore, a vertical triple tube heat exchanger with fractal fins was applied to enhance the heat transfer process of the LTES system. The performance of the LHE with fractal fins was discussed and compared to that with traditional rectangular fins. The results manifest that fractal fins can effectively improve the heat transfer rate of the LHE by providing more heat flow channels and heat transfer areas. The total melting time of PCM in the LHE with fractal fins is reduced by 27.3% compared to that with rectangular fins during the heat charging process. Furthermore, the structure of fractal fin is optimized through a heat transfer model and numerical simulation. It was apparent from the simulation results that the PCM melting time of the LHE with optimized fractal fins is reduced by 35.6% compared with that of rectangular fins. It was also proved that the dual-channel structure is used to reasonably arrange the charging and discharging processes, which can make the LTES system achieve better results.